System development of a time-of-flight spectrometer for surface analysis of materials - P. Junphong (2018)
This is original study on design the time-of-flight Rutherford backscattering spectrometry (TOF-RBS) technique for nano-material surface analysis with high resolution. At Fast Neutron Research Facility, FNRF, upgrading of the existing pulsed-beam accelerator from 150-keV of D+ to 280 keV of He+ was proposed to use for the most powerful method of a near-surface characterization of materials utilizing TOF-RBS. The beam transport was redesigned based on the new multicusp ion source which was designed the extraction and focusing system for optimization by the computer program KOBRA, and the existing beam pulsing system to provide He+ ion beam with a few nano-second width and 280-keV acceleration energy. Simulation was done by the computer program Beam Optics, resulting in the beam size at the target position of 1 mm in diameter. The measured beam size was 6 mm in diameter. The optimization of the target position was done by the PARMELA program, to be at 3.14m from the middle point of the buncher. Components, beam transport characteristics, beam optic simulation, and role of quadrupole magnet were explained with technical data listed. Design and test of the scattering chamber for TOF-RBS were shown with He-ion scattered spectra which were measured by the MCP detector. The quadrupole triplet was designed and constructed at FNRF. Development of TOF-RBS system was implemented in this study. Designing component, fabrication and installation to the accelerator system were completed. Beam extraction and He-scattering tests were done.